EFL Learners in Thailand: Content Analysis of Research Articles - Maravilla, Wes Harven G.; Maming, Jimmy Bernabe (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Due to recent shifts in the laws regulating Thailand's educational system, more study has been done on teaching English to EFL Thai pupils. Finding the frequent distribution of these studies in terms of their topics, publication years, writers, groups, and research methods is the main objective of this study. 56 articles were selected as the sample because it was discovered that they were content-specific in the context of English Language Acquisition in Thailand. Data was collected using the Article Information Rubric, and it was processed using Microsoft Excel. The following are the study's major conclusions: "Methods and Strategies" is the subject of most articles written by ELT scholars. The frequent distribution of publication years has changed significantly. The majority of college students were chosen as the group using the random selection technique. Mixed study techniques were used in the majority of the investigations. Questionnaires and conversations were used by researchers to gather data. The most frequently used form of data analysis in these studies is frequency and proportion charts.